Land Claims and Comanagement of Protected Areas in South Africa: Exploring the Challenges - Kepe, Thembela (Environmental management (New York), 2008)
Comanagement has recently become the most popular approach for reconciling land claims and biodiversity conservation in South Africa and beyond. Following the resolution of land claims on protected areas in South Africa, comanagement arrangements have been created between the relevant conservation authorities and the land claimant communities who are legally awarded tenure rights to the land. However, it is doubtful that these partnerships constitute success for the former land claimants. Using the case of a “resolved” land claim in Mkambati Nature Reserve, Eastern Cape Province, as well as insights from comanagement literature, this paper identifies and discusses three key possible reasons for the unimpressive performance of comanagement in reconciling land restitution and conservation. The first one is the origins of the comanagement idea in the conservation of high value natural resources (e.g., fisheries, forestry), rather than in or including concerns for resource rights. The second reason is the neglect of key conditions for successful comanagement, as discussed in the comanagement literature. The final reason is the ambiguity in settlement agreements, including the use of terminology and concepts that reinforce unequal power relationships, with the state emerging as the powerful partner. This paper concludes that, unless there is a serious reassessment of the comanagement idea as a way of reconciling land reform and conservation, and a possible review of settlement agreements that have relied on comanagement, both the integrity of the “successful land claimant's rights” and that of conservation remain under threat.